SYNTHESIS AND CHARACTERIZATION OF CELLULOSE ASCORBIC ACID RESIN AND ITS APPLICATION FOR REMOVAL OF HEAVY METAL IONS FROM EFFLUENT OF STEEL INDUSTRIES (International Journal of Engineering Sciences & Management Research, 2018)
A new cellulose based resin containing ascorbic acid group has been synthesized by Porath’s method of functionalization of polysaccharide. The resin was characterize by ion exchange capacity, thermogravimetric analysis and infra red spectroscopy. The distribution coefficient(Kd) of metal ions at different pH was studied using Batch equilibrium method. The resin has been found suitable for removal of heavy metal ions from steel industries